PENETRATION OF ANTIRETROVIRAL THERAPY INTO THE NERVOUS SYSTEM; COGNITIVE IMPAIRMENT IN HIV AND THE ROLE OF THE CNS AS A SANCTUARY SITE. A PROGRESS REPORT ON THE PARTITION STUDY. (29th November 2012) - Nightingale, S; Solomon, T
Abstract : Background: Combination antiretroviral therapy has revolutionised the treatment of HIV, however as these patients live for longer cognitive impairment is becoming increasingly prevalent—occurring in approximately 50% despite treatment. Indeed HIV is the leading cause of cognitive impairment in young adults worldwide. Persistence of HIV replication in the CNS has been implicated in this. Cerebrospinal fluid (CSF) drug penetration is limited and CSF drug levels can be as little as 1% of that in plasma. Furthermore, around 10% of patients have HIV RNA detectable in the CSF despite it being undetectable in blood. The Penetration of Antiretroviral Therapy Into the Nervous System (PARTITION) study is a major MRC-funded project currently recruiting over multiple UK sites. Aims: The main aims are to address the following questions: A. Why CSF antiretroviral drug levels vary so dramatically between individuals on the same drug regime? Host genotype is characterised, in particular polymorphisms in brain endothelial transporters, and compared to CSF drug levels in order to determine genetic predictors of CNS penetration. Neurocognitive function and CSF proteomic biomarkers are also assessed. B. Is the CNS a sanctuary site for HIV infection? Patients with detectable HIV in plasma despite seemingly adequate treatment are offered lumbar puncture to determine the proportion with higher levels of HIV in the CSF. Progress: We present the progress of this MRC-funded multicentre, UK-wide prospective study of patients with HIV across regional specialist HIV and neurological centres.